In vitro Evaluation of Different Chemical Fungicides for the Control of Rhizoctonia solani Kuhn - Dhami, Govinda; Maharjan, Demij (Journal of the Plant Protection Society, 2023)
An in vitro experiment was conducted for an evaluation of different chemical fungicides against Rhizoctonia solani using poisoned food technique at National Plant Pathology Research Centre, Nepal Agricultural Research Council (NARC) Khumaltar, Lalitpur. Pathogen was isolated from infected broad leaf mustard. The experiment was conducted in Completely Randomized Design (CRD) with three replications for each treatment. Seven fungicides as treatments, namely, Saaf (carbendazim 12% + mancozeb 63%), Bavistin (carbendazim 50%), Vacomil Plus (metalaxyl 15% + copper oxychloride 35%), Nativo (tebuconazole 50% + trifloxystrobin 25%), Sectin (fenamidone 10% + mancozeb 50%), Kingstival (dimethomorph 50%) and Topcare (azoxystrobin 50%) were taken for the evaluation. Two levels of concentrations (100 ppm and 200 ppm) were used for each fungicide and concentration was calculated based on active ingredients (a.i.) of the fungicides. All fungicides were used individually to study the rate of inhibition of R. solani on PDA media. At higher concentration 200 ppm, Bavistin, Nativo and Saaf showed complete inhibition of the mycelial growth of the pathogen whereas at lower concentration 100 ppm, Bavistin was only completely effective against the pathogen. Sectin and Topcare were also highly effective in inhibiting the growth of R. solani. The efficaces of Kingstival and Vacomil Plus against the pathogen were much lesser than others. The active ingredients carbendazim, tebuconazole, mancozeb and trifloxystrobin showed the highest degree of mycelial growth inhibitions compared to others. The fungicides that found to be effective for inhibition of mycelial growth of R. solani in this study should be further tested in the field conditions in order to verify their efficacies as well as to determine their optimum application doses.